DEVELOPMENT OF A CULTURE OF SAFETY IN UNIVERSITIES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses the importance of fostering a culture of safety in higher education institutions in the context of contemporary challenges and crises. The author emphasizes that education plays a key role in adapting individuals to social and technological changes. The safety principle is highlighted as a central element of the educational process, aimed at reducing the impact of negative factors and shaping a resilient society.